Experimental Investigation of Bow Slamming on a Ship: The Effect of Weight and Impact Angle - Baso, Suandar; Himaya, Andi Nadia; Samman, Faizal Arya; Anggriani, Andi Dian Eka; Rosmani, Rosmani (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2021)
The impact pressure induced by slamming can imply physical damage on a ship. The high probability of the slamming impact is on the bow part in the actual sea state. In this present study, the slamming induced pressure on the bow flare of a ship have been investigated through the experiment. The experiment was schemed by the dropping test based on free-falling body in the wave tank, wherein the bow of the ship model was inclined in several impact angles 0° to 30° to the free-water surface. To measure slamming impact pressure acting on the bow flare, the piezoelectric sensors S1, S2, S3, S4 were attached to the bow section and installed on a computer. As the obtained results, the impact pressure on bow flare occurred in a short time duration caused by slamming. The discrepancy of the peak impact pressure between ship model weight of 2.42 kg and 7.29 kg for the impact angle 0° is 70.36% S1, 69.52% S2, 68.97% S3, and 68.34% S4. For the relative impact angle of 30°, the discrepancy is 67.02% S1, 65.73% S2, 58.51% S3, and 48.21% S4. The tendency of the peak pressure coefficient at the sequenced impact points S1, S2, S3, S4 is similar for all impact angles 0°, 10°, 20°, and 30°. The peak pressure coefficient due to the full load condition is highest in the nearest bottom part, and the peak pressure coefficients due to the lightship condition highest in the nearest bottom part caused by the small impact angle.